The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1590/1806-9282.63.12.1065
|View full text |Cite
|
Sign up to set email alerts
|

Elevated neutrophil-to-lymphocyte ratio in the diagnosis of Hashimoto's thyroiditis

Abstract: Increased NLR may be useful as an indicator of the presence of HT, especially in complicated cases. NLR is inexpensive and easy to determine. Larger, prospective studies are required to determine its usefulness in assessing diagnostic potential and treatment outcomes in HT patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 34 publications
2
110
0
Order By: Relevance
“…In another study, it has been suggested that NLR may be more valuable than other markers in anticipating bacteremia under emergency conditions. NLR has been also shown to be present as a marker in infl ammatory diseases (17). In our study, we have reached the conclusion that NLR can be used as an indicator of infl ammation by reasoning that NLR was higher in the infected group compared to the non-infected group.…”
Section: Discussionsupporting
confidence: 51%
“…In another study, it has been suggested that NLR may be more valuable than other markers in anticipating bacteremia under emergency conditions. NLR has been also shown to be present as a marker in infl ammatory diseases (17). In our study, we have reached the conclusion that NLR can be used as an indicator of infl ammation by reasoning that NLR was higher in the infected group compared to the non-infected group.…”
Section: Discussionsupporting
confidence: 51%
“…Whereas, in a study by Cıray et al there was no difference among NLR between the patients with or without diabetic retinopathy (23). Also there are studies in which Hashimoto thyroiditis, which is one of the autoimmune thyroid diseases, is found to be signifi cantly higher than in the NLR and PLR control group (24) and before treatment than after levothroxine replacement (22). Despite the development of a similar autoimmune process with Graves' disease in Hashimoto thyroiditis, the thyroid hormone levels and the used medication are different.…”
Section: Discussionmentioning
confidence: 89%
“…It is known that white blood cells differ in systemic inflammation, such as neutrophilia and lymphopenia. 6 This inflammatory response and tissue necrosis leads to fibrosis and poor recipient vascularity, which likely has a key role in deficient wound healing, which, in turn, threatens urethroplasty success. 22 In a related study of 208 patients with a history of urethral stricture after transurethral resection of the prostate, it was shown that the NLR was relatively higher in relapsed patients but not significant.…”
Section: Discussionmentioning
confidence: 99%